Associations Between Physician Continuous Professional Development and Referral Patterns: A Systematic Review and Meta-Analysis. (27th April 2022) - Cook, David A.; Stephenson, Christopher R.; Pankratz, V. Shane; Wilkinson, John M.; Maloney, Stephen; Prokop, Larry J.; Foo, Jonathan
Abstract : Purpose: Both overuse and underuse of clinician referrals can compromise high-value health care. The authors sought to systematically identify and synthesize published research examining associations between physician continuous professional development (CPD) and referral patterns. Method: The authors searched MEDLINE, Embase, PsycInfo, and the Cochrane Database on April 23, 2020, for comparative studies evaluating CPD for practicing physicians and reporting physician referral outcomes. Two reviewers, working independently, screened all articles for inclusion. Two reviewers reviewed all included articles to extract information, including data on participants, educational interventions, study design, and outcomes (referral rate, intended direction of change, appropriateness of referral). Quantitative results were pooled using meta-analysis. Results: Of 3, 338 articles screened, 31 were included. These studies enrolled at least 14, 458 physicians and reported 381, 165 referral events. Among studies comparing CPD with no intervention, 17 studies with intent to increase referrals had a pooled risk ratio of 1.91 (95% confidence interval: 1.50, 2.44; P < .001), and 7 studies with intent to decrease referrals had a pooled risk ratio of 0.68 (95% confidence interval: 0.55, 0.83; P < .001). Five studies did not indicate the intended direction of change. Subgroup analyses revealed similarly favorable effects for specific instructional approaches (including lectures, small groups, Internet-based instruction, and audit/feedback) and for activities of varying duration. Four studies reported head-to-head comparisons of alternate CPD approaches, revealing no clear superiority for any approach. Seven studies adjudicated the appropriateness of referral, and 9 studies counted referrals that were actually completed (versus merely requested). Conclusions: Although between-study differences are large, CPD is associated with statistically significant changes in patient referral rates in the intended direction of impact. There are few head-to-head comparisons of alternate CPD interventions using referrals as outcomes.